Vertical collective action : addressing vertical asymmetries in watershed management (2015)
Watersheds and irrigation systems have the characteristic of connecting people vertically by water flows. The location of users along these systems defines their role in the provision and appropriation of water which adds complexity to the potential for cooperation. Verticality thus imposes a challenge to collective action. This paper presents the results of field experiments conducted in four watersheds of Colombia (South America) and Kenya (East Africa) to study the role that location plays in affecting trust and cooperation in decisions regarding to provision and appropriation of water. We recruited 639 watersheds inhabitants from upstream, midstream and downstream locations in these basins and conducted two field experiments: the Irrigation Game and the Water Trust Game. The Irrigation Game (Cardenas et al, 2013; Janssen et al, 2011) involves decisions regarding to the provision and appropriation of water where the location in the system is randomly assigned. The Water Trust Game is an adaptation of the trust game (Berg et al 1995) framed around water and economic compensation flows where we explicitly reveal the actual upstream or downstream location of the two players. The results of the two games show that location affect water provision and distribution and that reciprocity and trust are key motivations for upstream-downstream cooperation. Yet, both experiments also suggest that the lack of trust from downstream players towards upstream players may restrict the possibilities of cooperation among watershed users.